2019
DOI: 10.1017/s1431927618015647
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Sense Organs of Ovipositors of an Endoparasitoid Aprostocetus causalis and an Ectoparasitoid Quadrastichus mendeli in Leptocybe spp.

Abstract: Little is known of the olfactory mechanisms of host detection in the ovipositors of endoparasitoids and ectoparasitoids. An endoparasitoid Aprostocetus causalis La Salle & Wu (Hymenoptera: Eulophidae) and an ectoparasitoid Quadrastichus mendeli Kim & La Salle (Hymenoptera: Eulophidae: Tetrastichinae) are the two parasitoids of the eucalyptus gall wasp Leptocybe spp. Structures and sense organs of ovipositors of A. causalis and Q. mendeli were studied using scanning and transmission electron microscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…In addition, several studies have shown that the sensilla on ovipositor also plays a crucial role in the process of spawning in female wasps (Huang et al, 2019), which is synergistic with the function of antennae. Therefore, besides the functional verification test for antennae sensilla, meanwhile, the morphology and ultrastructure of ovipositor sensilla of the parasitic wasp B. dioryctriae need be investigated in our future study, in order to make an overall identify for the sensilla involved in host location and oviposition of B. dioryctriae .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have shown that the sensilla on ovipositor also plays a crucial role in the process of spawning in female wasps (Huang et al, 2019), which is synergistic with the function of antennae. Therefore, besides the functional verification test for antennae sensilla, meanwhile, the morphology and ultrastructure of ovipositor sensilla of the parasitic wasp B. dioryctriae need be investigated in our future study, in order to make an overall identify for the sensilla involved in host location and oviposition of B. dioryctriae .…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the stinger/ovipositor sensilla have been studied more in parasitic hymenopterans, where they have been classified as mechanoreceptors and chemoreceptors (and/or dual function mechano-chemosensors) as reported by Gal et al (2014) in Ampulex compressa , by Dweck et al (2008) in H. hebetor , and by Huang et al (2019) in Aprostocetus causalis and Quadrastichus mendeli .…”
Section: Discussionmentioning
confidence: 99%
“…Because the sensilla must be connected to the central nervous system via sensory neurones, the presence of the sensilla on honey bee lancets shows that they are not just simple cuticular needles, but live organs. Such an assumption appears reasonable, but it is surprisingly under-documented in the literature, with the majority of the evidence relating to the parasitoids indicated above (Dweck et al, 2008;Gal et al, 2014;Huang et al, 2019). This may be due to the difficult preparation of the hard stinger for TEM analysis: the bee stinger is a small, narrow hard tube through which fixation and other tissue-processing solutions for TEM are difficult to penetrate.…”
Section: Functional Morphology and Anatomy Of Worker And Queen Bee St...mentioning
confidence: 99%
“…Among them, the ovipositor of hymenopteran insects comprises ventral and internal valves, among which the dorsal valve is wide and the ventral valve surface is concave to form an ovipositor sheath to contain it. The ovipositor of parasitic wasps is needle‐shaped (Huang et al, 2019), which lay eggs in plant tissues (Yang et al, 2014) or other insects (Gomez Duran & van Achterberg, 2011). The ovipositor of hemipteran insects (except aphids and scale insects) is mainly composed of dorsal and ventral valves, and the dorsal valve forms an ovipositor sheath to wrap around the ovipositor that stretches out and slides up and down when laying eggs, allowing its gradual insertion into the plant tissue to lay eggs (Zhong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%